Multi-stakeholder approach needed to tackle cyberthreats - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2016)
Being a hyper-connected society, our national security is also increasingly being redefined by threats in the cyberspace. Cyberattacks have evolved from a nontraditional security threat to a new domain of intense conflict, involving deception and sabotage.